The 2018 peoples' global conference against the International Monetary Fund and World Bank in Bali, Indonesia - Enrile, Ivan Phell (Asia Pacific Research Network, 2019)
This book is a compilation of the analyses and insights of peoples' movements and their communities that are directly affected by the deleterious impacts of the IMF-World Bank's policies and projects. It is also a documentation of the courage of peoples' movements defending their rights and sovereignty in the face of heavy repression